Production and Performance of Triploid Oysters for Aquaculture - Huiping Yang; Natalie Simon; Leslie N. Sturmer (EDIS)
This 9-page fact sheet written by Huiping Yang, Natalie Simon, and Leslie Sturmer and published by the Program in Fisheries and Aquatic Sciences of the UF/IFAS School of Forest Resources and Conservation focused on basic aspects of triploid oyster aquaculture, including the general oyster aquaculture industry, the approaches for triploid induction, performance of triploids, and correlated ploidy determination to convey basic knowledge of triploid oyster aquaculture to the oyster industry and the general public. http://edis.ifas.ufl.edu/fa208